Respuesta :
Answer:
-4x^2-6x+6
Step-by-step explanation:
We are asked to subtract g from f.
So the problem is:
[8x^2-2x+3]-[12x^2+4x-3]
So I'm going to distribute and write without [].
8x^2-2x+3-12x^2-4x+3
Now I'm going to pair up any like terms:
8x^2-12x^2-2x-4x+3+3
Simplifying:
-4x^2-6x+6
Answer: The correct option is
(C) [tex]h(x)=-4x^2-6x+6.[/tex]
Step-by-step explanation: We are given the following two functions :
[tex]f(x)=8x^2-2x+3,~~~~~g(x)=12x^2+4x-3.[/tex]
We are to find the value of h(x) if h(x) = f(x) - g(x).
To find the value of h(x), we must subtract the expression of g(x) from the expression of f(x).
The value of h(x) can be calculated as follows :
[tex]h(x)\\\\=f(x)-g(x)\\\\=(8x^2-2x+3)-(12x^2+4x-3)\\\\=8x^2-2x+3-12x^2-4x+3\\\\=-4x^2-6x+6.[/tex]
Thus, the required value of h(x) is [tex]-4x^2-6x+6.[/tex]
Option (C) is CORRECT.